Analisis Kelayakan Finansial Usaha Ternak Ayam Broiler pada Peternak Mitra PT Mitra Sinar Jaya di Kota Atambua - Lole, Ulrikus R.; Seran, Alfiani; R. D. Ratu, Maria; Tiro, Melkianus (Green Publisher Indonesia, 2024)
A research was conducted with objectives to analyze income and financial feasibility of broiler farming business run by partner farmers of PT Mitra Sinar Jaya in Atambua City. The research method used was survey. Method of determining sample comprises two stages. First, selection of nine villages sample, purposively, which from three sub-districts in Atambua City represented by three villages. Second, selection of four farmers as respondents from each village, so total number of the respondents were 36 farmers. The selection of the respondents was done based on non-proportional random sampling. Criteria of the respondents were: 1) partner of PT Mitra Sinar Jaya, and 2) the respondents have been raising the broiler farm at least for two years. Primary data were obtained through observation and direct interview based on prepared questionnaires. Secondary data were obtained based on documentation technique from report of relevant institutions and references. Methods of data analysis applied were income analysis and financial feasibility analysis using investment criteria namely B/C, BEPIDR, BEP unit, and PP criteria. The results showed that the average income gained by each farmer from the partnership pattern of broiler farming business was 63,313,679.03/year. Further, the financial analysis showed that the farm B/C was 1.15, BEPunit was 39.33 ST, BEPIDR 55,972,941.18,- and PP was 2.6 years. In conclusion, the broiler farming business in Atambua City was profitable and financially feasible. Therefore, this business needs to be developed and improved.